2010
DOI: 10.2741/3642
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the control of human skin blood flow

Abstract: Human exposure to cold and heat stimulates cutaneous vasoconstriction and vasodilation via distinct sympathetic reflex and locally mediated pathways. The mechanisms mediating cutaneous vasoconstriction and vasodilation are impaired with primary aging, rendering the aged more vulnerable to hypothermia and cardiovascular complications from heat-related illness, respectively. This paper highlights recent findings discussing how age-related decrements in sympathetic neurotransmission contribute directly to thermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 124 publications
(193 reference statements)
1
81
1
3
Order By: Relevance
“…This is consistent with the finding that, in humans, reflex muscle vasoconstriction was attenuated with aging, even though MSNA was increased and that cutaneous vasoconstriction was blunted by aging and no longer included an NPY component. 13,14 To our knowledge, ours is the first evidence that even modest aging attenuates the NPY component of sympathetic muscle vasoconstriction. The mechanisms are not clear.…”
Section: Effects Of Agingmentioning
confidence: 68%
See 1 more Smart Citation
“…This is consistent with the finding that, in humans, reflex muscle vasoconstriction was attenuated with aging, even though MSNA was increased and that cutaneous vasoconstriction was blunted by aging and no longer included an NPY component. 13,14 To our knowledge, ours is the first evidence that even modest aging attenuates the NPY component of sympathetic muscle vasoconstriction. The mechanisms are not clear.…”
Section: Effects Of Agingmentioning
confidence: 68%
“…11,12 But chronically raised MSNA also occurs during aging and is accompanied by reduced reflex vasoconstriction and loss of NPY involvement in skin. 13,14 However, in young men at high altitude, chronic hypoxia caused an increase in tonic MSNA, tonic muscle vasoconstriction, and hypertension that persisted on descent to sea level. 15,16 Further, vasoconstrictor responses evoked by sympathetic activation were blunted in acute and chronic hypoxia in adult rats and humans [17][18][19] ; this was attributed to impaired vasoconstriction to NE and adenosine triphospate, but preservation of the NPY component.…”
mentioning
confidence: 99%
“…It has been reported that age, pre-operative SBP, www.bionursingjournal.or.kr and heart rate influence intraoperative hypothermia in laparotomic surgery [3,4]. Advancing age decreases the responsiveness of the sympathetic nerves to hypothermia [28] and leads to incomplete thermoregulatory vasoconstriction and decreased metabolic heat production [29]. However, presently age did not influence intra-operative hypothermia during the 2 hours after pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…This fact could be due to loss of vascular tone as a consequence of the strong presence of increased production of oxygen free radicals, besides poor sympathetic vasoconstriction reflex (Camici et al, 2011;Camici et al, 2015;Holowatz et al, 2010). As a consequence, older adults would be less able to adequately thermoregulate and repair cutaneous wounds (Tew et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity, considered as a cornerstone in the primary and secondary disease prevention across different conditions, is a lifestyle factor related to the cutaneous microcirculation (Tew et al, 2012) which can improve circulation of blood with amelioration of the contraction in skeletal muscles, aiding supply of oxygen and ameliorating oxidative metabolism. The mechanisms underlying the increased blood flow during physical activity include (i) better adaptation of the vascular endothelial function by the likely effect of nitric oxide, (ii) excitation and signaling ATP, (iii) improve of the sympathetic reflexes (Holowatz et al, 2010;Nyberg and Hellsten 2016) and decrease of arterial stiffness (Endes et al, 2016). In order to reach these effects numerous activities (i.e.…”
Section: Introductionmentioning
confidence: 99%